واقع تجارب الدول الأوربية في فتح نوافذ اسلامية – المعوقات و التحديات - الزين, يونس; حفوظة, الامير عبد القادر (جامعة الوادي- University of Eloued, 2017)
We address in this paper and the reality of the application of Islamic banking financing at the level of European countries formats such as opening Islamic windows in conventional banks or opening Islamic banks, where we were to the reality of what we have reached the European countries from the application of these circumstances the last on the banking systems level as well as the reasons and motives listed that led to the adoption of these circumstances funding formulas and what Almakoqat and the challenges they face.
The reality of the experiences of European countries in opening Islamic windows Constraints and challenges
مقال
Keywords: Islamic banks, the experiences of European countries.